2017
DOI: 10.1186/s12916-017-0942-1
|View full text |Cite
|
Sign up to set email alerts
|

The cost determinants of routine infant immunization services: a meta-regression analysis of six country studies

Abstract: BackgroundEvidence on immunization costs is a critical input for cost-effectiveness analysis and budgeting, and can describe variation in site-level efficiency. The Expanded Program on Immunization Costing and Financing (EPIC) Project represents the largest investigation of immunization delivery costs, collecting empirical data on routine infant immunization in Benin, Ghana, Honduras, Moldova, Uganda, and Zambia.MethodsWe developed a pooled dataset from individual EPIC country studies (316 sites). We regressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In this analysis we draw on a unique data set of immunization service costs collected as part of the EPIC studies, funded by the Bill & Melinda Gates Foundation to fill the knowledge gap around immunization costs and financing. These data describe the costs and performance of a large, representative sample of immunization sites in Benin, Ghana, Honduras, Moldova Uganda and Zambia [22][23][24]. Using these data, we investigate different quantitative approaches for estimating the efficiency of immunization sites, to describe their relative performance and draw conclusions about their utility for efficiency evaluation within infant immunization programs, as well as provide summary estimates of efficiency at a country level and describe within-country variation in efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In this analysis we draw on a unique data set of immunization service costs collected as part of the EPIC studies, funded by the Bill & Melinda Gates Foundation to fill the knowledge gap around immunization costs and financing. These data describe the costs and performance of a large, representative sample of immunization sites in Benin, Ghana, Honduras, Moldova Uganda and Zambia [22][23][24]. Using these data, we investigate different quantitative approaches for estimating the efficiency of immunization sites, to describe their relative performance and draw conclusions about their utility for efficiency evaluation within infant immunization programs, as well as provide summary estimates of efficiency at a country level and describe within-country variation in efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The studies in Benin and Ghana found doses administered as significant determinants of cost; however, salary was not significantly associated [5] , [6] . The multi country study on determinants of immunization costs also found that higher health facility level was associated with higher costs probably because of differences in availability of staff and infrastructure [17] . Higher service volume was significantly associated with lower average cost while greater distance for vaccine collection was associated with higher facility cost.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the measurement error in wastage rate, we dropped this variable from our regression model. The multi-country study on determinants of immunization cost also could not include vaccine wastage rate as an explanatory variable because of data limitations [17] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations